Rozwój kompetencji komunikacyjnej studenta specjalności ‘Język angielski w biznesie i zarządzaniu’ oraz ‘Lektor i tłumacz języka angielskiego’ w przestrzeni uczelni o profilu praktycznym - Bielak, Marlena Iwona (Scripta Neophilologica Posnaniensia, 2022)
The paper is devoted to the problem of shaping communicative competence at the level of higher education neoophilological studies with regard to the expectations of the socio-economic environment. Therefore, the publication outlines the evolution of the idea of communicative competence on the basis of selected theories and describes the tendency of moving away from the Humboldtian model of university towards an approach that takes into consideration the requirements of the socio-economic environment in order to reflect them in study programmes. In relation to the above concept, the paper also demonstrates factors determining the development of students’ communicative competence in the space of a practical profile university. The research presents an analysis of the development of communicative competence of the student of first-cycle studies conducted at a practical profile university, specialization: ‘The English language in business and management’ and ‘Instructor and translator of the English language’.